The impact of the Spanish Civil War on Britain : war, loss and memory - Buchanan, Tom, 1960- (Brighton [England] ; Portland, Or. : Sussex Academic Press, 2007)
"Published to coincide with the 70th anniversary of the outbreak of the Civil War, this book makes a timely contribution to the continuing debates about the political ideologies and passions of the 1930s. New archival sources illuminate pivotal moments in Britain's relationship with the conflict, such as the bombing of Guernica, while there is a discussion of the importance of loss and memory during the war itself and in subsequent decades."--Jacket.
"A far away country of which we know nothing"? British perceptions of Spain and its civil war, 1931-1939; Journalism at war: George Lowther Steer, Guernica and the resistance to fascist aggression; The masked advance: politics, intrigue and British medical aid for the Spanish Republic; The lost art of Felicia Browne; Mobilising art: British artists and the Spanish Civil War; The death of Bob Smillie, the Spanish Civil War and the eclipse of the Independent Labour Party; Loss, memory and the British "volunteers for liberty"; My country right or left: John Langdon-Davies and Catalonia; Spain rediscovered: British perceptions of Franco's Spain and the advent of mass tourism, 1945-1975; The Spanish Civil War in British politics since 1939; Index.
Includes bibliographical references (pages 197-257) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Great Britain -- Social life and customs -- 20th century; Spain -- History -- Civil War, 1936-1939 -- Foreign public opinion, British; Spain -- History -- Civil War, 1936-1939 -- Influence; British -- Spain -- History -- 20th century; Spain -- History -- Civil War, 1936-1939 -- Participation, British; Great Britain -- Politics and government -- 1936-1945.; Grande-Bretagne -- Mœurs et coutumes -- 20e siècle.; Espagne -- Histoire -- 1936-1939 (Guerre civile) -- Influence; Britanniques -- Espagne -- Histoire -- 20e siècle.; Grande-Bretagne -- Politique et gouvernement -- 1936-1945.; British; Influence (Literary, artistic, etc.); Manners and customs; Military participation -- British; Politics and government; Public opinion, British; Great Britain; Spain; Britter -- historia -- Spanien -- 1900-talet.; Spanska inbördeskriget 1936-1939 -- influenser; Spanska inbördeskriget 1936-1939 -- brittiskt deltagande; Storbritannien -- vardagsliv och traditioner -- 1900-talet.; Storbritannien -- politik och förvaltning -- 1936-1945.; 1900-1999; History